HEALTH EFFECTS OF AIR POLLUTION ON PREGNANCY - HAUWA UMAR USMAN, HAUWA UMAR USMAN; ABUBAKAR IBRAHIM HASSAN, ABUBAKAR IBRAHIM HASSAN (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
An Addition of harmful substances to the atmosphere resulting in damage to the environment, human health and quality of lifeis termed air pollution. Air pollution affects pregnancy in totality, it affect the mother and child. This paper addresses the health effects of air pollution on pregnancy, human activities that result to air pollution, major sources of air pollution and tips on how to prevent/control air pollution when pregnant. It is recommended among others that pregnant women need to be constantly enlightened about the effects polluted air as on them and theirfetus, through antenatal and postnatal visits to the hospital.